2018
DOI: 10.1002/lary.27179
|View full text |Cite
|
Sign up to set email alerts
|

Management of myringitis: Current concepts and review

Abstract: No well-designed randomized studies have assessed optimal treatments. Although surgery showed better treatment results than topical agents and laser-assisted treatment, the wide range of resolution rates indicates that proper patient selection is needed. Further studies are needed to improve the current understanding and management of myringitis. Laryngoscope, 128:2157-2162, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This showed that the 1 per cent diluted vinegar ear drops seemed to be more effective than the 1 per cent chloramphenicol ear drops for treating granular myringitis, but the difference between groups failed to achieve statistical significance. This insignificant result is probably a result of the small number of participants in each subgroup since the previous positive study 5 that we used for sample size calculation used a higher concentration of diluted vinegar with the irrigation method.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This showed that the 1 per cent diluted vinegar ear drops seemed to be more effective than the 1 per cent chloramphenicol ear drops for treating granular myringitis, but the difference between groups failed to achieve statistical significance. This insignificant result is probably a result of the small number of participants in each subgroup since the previous positive study 5 that we used for sample size calculation used a higher concentration of diluted vinegar with the irrigation method.…”
Section: Discussionmentioning
confidence: 91%
“…Current treatment regimens include topical antibiotics, steroid ear drops, diluted vinegar solution, diluted hydrogen peroxide, 5-fluorouracil, Castellani solution, chemical cauterisation and curettage of the granulation. 1,5 The popular topical ear drops used in our institution are topical antibiotics with or without steroids. However, with these formulations, fungal accumulation in the ear canal might sometimes occur.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no single therapeutic regimen has been determined to be successful in the management of granular myringitis. [5] In our study, we compared the effect of caustic agent cauterization and CO 2 laser vaporization. We had all patients underwent topical otic drops previous to the surgical treatment at least one month, and the total remission rate was only 22.3% (29/130).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review highlighted the non-existence of any randomized controlled trial in GM ( Chung et al, 2018 ). By comparing all the treatment options, surgery seems to be the most effective treatment option ( Chung et al, 2018 ). However, the topical agents form an essential line of therapy even now, having been used as an adjunct with either of laser therapy or surgery.…”
Section: Granular Myringitismentioning
confidence: 99%